2013
DOI: 10.1111/boj.12124
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic and morphological differentiation in the European species complex ofRosa sherardii,R. mollisandR. villosa(RosasectionCaninaesubsectionVestitae)

Abstract: The polyploid species complex of Rosa villosa sensu lato (Rosa section Caninae subsection Vestitae) consists of three morphologically similar polyploid species: R. sherardii, R. mollis and R. villosa. Whereas R. sherardii is distributed in central Europe, R. mollis and R. villosa represent a vicariant species pair occurring in northern Europe and in mountains of central and eastern Europe, respectively. In this study we analysed multiple data sets (morphology, cytology, microsatellites, AFLP and plastid DNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
2
12
0
1
Order By: Relevance
“…For H. lahue, the effect of polyploidy on the genetic structure of populations must also be considered. The polyploidy itself exerts a differentiating effect among populations, and it is known that recurrent polyploidy can create genetically distinct populations (Soltis and Soltis 2000;Soltis et al 2004;Kellner et al 2014). Moreover, as here other studies have demonstrated differences among cytotypes at genetic and morphological levels (Guldahl et al 2005;Keeler and Davis 1999;Tacuatiá et al 2012b;Khadivi-Khub et al 2014).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…For H. lahue, the effect of polyploidy on the genetic structure of populations must also be considered. The polyploidy itself exerts a differentiating effect among populations, and it is known that recurrent polyploidy can create genetically distinct populations (Soltis and Soltis 2000;Soltis et al 2004;Kellner et al 2014). Moreover, as here other studies have demonstrated differences among cytotypes at genetic and morphological levels (Guldahl et al 2005;Keeler and Davis 1999;Tacuatiá et al 2012b;Khadivi-Khub et al 2014).…”
Section: Discussionsupporting
confidence: 65%
“…However, in other situations, the discriminating power of morphometric analysis is low. This was the case for other Iridaceae, for which morphometric analysis was unable to discriminate a species complex (Arafeh et al 2002;Sapir et al 2002;Saad and Mahy 2009) or alternative taxonomic group [e.g., in Rosa complex, Kellner et al (2014)]. In this study, despite morphometry being usless to infer relationships among cytotypes, combining some variables can be useful for preliminary and simple identification of cytotypes (Online Resource 3), particularly combining measurements (width and length) of the outer tepals.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Well documented chromosome counts are known from western and continental Europe, but no records exist from Norway. Both R. mollis and R. sherardii belong to subsection Vestiate Christ within section Caninae, and the taxonomic separation of the species within this group is known to be challenging (Henker , Kellner et al ). The hybrid taxa R .…”
Section: Overview Of Chromosome Counts From Literature For Selected Smentioning
confidence: 99%